The Causality Effect of Foreign Direct Investment on Economic Growth in Sub Saharan Africa: An Empirical Evidence from Chad Using ARDL Approach - Ganama MOUSTAPHA GUEME; Maimunah Binti ALI; Khalil KAYA; Hissein ARABY NOUR and Khadar Ahmed DIRIE (Communications of International Proceedings, 2020)
Foreign direct investment (FDI) towards developing nations is eventually intended to help host countries attain sustainable economic growth. As such, the recipient country ultimately achieves poverty reduction and improved human development. Over the past decades, the justification for increasing foreign direct investment to developing and under developing countries have constantly grabbed the attention among scholars and researchers. However, despite inflow of FDI towards the Sub Sharan African (SSA) countries, economic growth is still inconsistent in these regions. And even though foreign direct investment in Chad has grown in the recent years, the country still faces development constraints. This study aims to assess the effect of FDI on economic growth in Chad using time series data collected from the World Bank from 1980 to 2019. The autoregressive distributed lag (ARDL) and error correction (ECM) models were estimated among the variables. Hence, both the long run and short run dynamics regression estimates revealed that FDI has a significant effect on economic growth in Chad within the period. Nonetheless, there is a strong sign of convergence towards long run equilibrium as the speed of adjustment is significantly high at -122.7133%. The findings explain evidence of a uni-directional causality (one-way) running from FDI to economic growth. Furthermore, the paper recommended that both public and private foreign investors should invest in specific needs and exhaust every prudential step in making sure the inflow of FDI is efficiently used for the target aimed to boost the overall economic growth of the country especially by enhancing infrastructure, openness, and inflation target.
Keywords: Foreign direct investment; Economic growth; ARDL; ECM; Republic of Chad.